A Promotion Role of MIR31 in the Process of Vocal Fold Wound Healing - Haizhou Wang; Wen Xu (PPAR Research)
The role of MIR31 in the wound healing process, specifically in vocal fold wound healing (VFWH), remains uncertain despite its potential to facilitate the process. In this study, we first constructed a literature-based pathway to examine both the positive and negative effects of MIR31 on wound healing. We then conducted animal experiments on 20 rats to investigate MIR31 expression at different time points (1, 4, and 8 weeks) after vocal fold injury. Co-expression analysis and pathway analysis were performed to explore the potential function of MIR31 in VFWH. The literature-based pathway suggested that MIR31 could both impede and promote the wound healing process by regulating 14 and 47 wound healing upstream regulators, respectively. However, the rat experiment indicated that MIR31 expression significantly increased after vocal fold injury (p<5.65×10−5) but decreased in the late stage of VFWH compared with the early and middle stages (p<5.40×10−3. Strong co-expression was observed between MIR31 and 17 VFWH-significant genes (Pearson correlation coefficient ∈ (0.63, 0.83)), primarily involved in collagen production. Overall, our findings suggest that MIR31 plays a critical role in VFWH, particularly in collagen synthesis and other biological processes, which warrant further investigation.